(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
A kind of silica nanofibers (SNF) mats with superhydrophobicity and superlipophilicity as well as excellent heat resistance, had been prepared by modifying of 1, 1, 1, 3, 3, 3-hexamethyldisilazane on electrospun SNF mats. The effects of heat treatment time on properties of modified SNF mats were investigated by scanning electron microscopy, nitrogen absorption analysis, X-ray photoelectron spectroscopy, and contact angle measurement. With high specific surface area 240.1 m2/g, the optimal modified SNF mat approached water contact angle 153.2° and fuel contact angle 0°, meanwhile, the hydrophobic and lipophilic tolerable temperature reaching 450℃, which opened a new way to improve heat resistance of fuel-water filter paper.